PENGARUH PROGRAM PELATIHAN DASAR KOMPUTER TERHADAP KEMAMPUAN MENGOPERASIKAN MICROSOFT OFFICE DI SMP N 5 KUPANG TIMUR - Khatrin Juliani Taku Neno; Jhon Enstein (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
One of the basic skills in the current digitalization era is the skill to operate a computer, especially operating Microsoft Office. The problems found in the field are the lack of school facilities in providing computers, lack of computer ownership by each student and limited learning time to deepen Microsoft Office practicum. One solution to overcome this is to hold a basic computer training program. Therefore, the purpose of this study was to determine the extent of the influence of the training program on computer operating skills. This research is a quantitative research with a type of experimental design. The sample in this study was 22 class VII students of SMP N 5 East Kupang. Data collection techniques were carried out by means of skills tests and non-tests (observation). The data analysis technique uses a prerequisite analysis test which consists of a normality test and a variance homogeneity test. Furthermore, using the N-Gain test to see the effect of basic computer training programs on students' skills in operating Microsoft Office. The results showed that the significance value of the paired samples test was 0.000 <0.05, which means that there was an influence on the basic computer training program on the ability of students at SMP N 5 Kupang Timur in operating Microsoft Office. It can also be seen from the N-Gain score of 58.2% that the basic computer training program conducted was quite influential in improving the skills of SMP N 5 Kupang Timur students in operating Microsoft Office.